The Principal's Role in Developing Inclusive Learning Environment at SMPN 1 Gringsing, Batang District - Siti Rodiyah; Athi Aliyatus Sya'ni; Soedjono Soedjono (ITScience (Information Technology and Science), 2024)
This research explores the role of school principals in developing an inclusive learning environment at SMPN 1 Gringsing in Batang district. Inclusive education aims to provide equal learning opportunities for all students, including children with special needs. However, implementation in this school faces challenges such as limited disability-friendly facilities, lack of teacher training, and social stigma. A descriptive qualitative approach was used in this study, with data collection techniques including in-depth interviews, participatory observation, and documentation. The results show that principals have a strong commitment to inclusive education through strategies such as the formation of inclusion teams, curriculum modifications, and collaboration with parents and communities. Principals also play a pivotal role in fostering a supportive school culture by encouraging teachers to adopt inclusive practices and ensuring that students with special needs feel welcome and supported in their learning environment. However, limited resources and understanding are the main obstacles, hindering the full implementation of inclusive programs. This study recommends improving facilities, teacher training, effective communication with parents, and developing special programs to strengthen inclusive education. Additionally, partnerships with external organizations and local governments are crucial to providing technical and financial support for sustainable inclusive practices. Optimal implementation of inclusive education is expected to provide access to quality education for all students, including children with disabilities, in a regular school environment. This research provides a comprehensive picture of the principal's role in developing an inclusive learning environment and highlights the challenges and hopes for the future to improve the quality of education for all students.